Can history be used to build the nation? An analysis of the idea of a compulsory school history curriculum in post-apartheid South Africa (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
Despite the critical role of education in peacebuilding, few studies in South Africa have interrogated the role of the school history curriculum on nation-building, leaving a critical gap in our understanding of the impact of a wrongly designed, developed, and implemented history curriculum. This conceptual paper, informed by the sociological foundations of education, responds to one question underpinning this study: What opportunities and threats are there for making school history compulsory in a country composed of diverse histories? Using the case of South Africa, the paper deploys document analysis to explore the risks and possibilities for making a school history curriculum compulsory. The findings replicate that making school history compulsory can be useful for nation-building. The study also argues that school history has two faces: rather than promoting nationalism and social cohesion it can also be a wedge that divides and fragments the society. Considering these findings, the study argues that the curriculum is a product of people and recommends that the school history curriculum in any country must be a selection from the history of all people. Significantly, this study extends and enriches the yet small number of studiesthat debate making school history compulsory for nation-building. The paper contributes practical insights into how the school curriculum can be designed, developed, and implemented for the good of the whole nation.